In-situ generated high-stability nano metal particle dispersion reinforced Mo alloy and preparation method thereof
The preparation of in-situ high-stable nanometal particles diffusion-enhanced Mo alloys through powder metallurgy method solves the problem that traditional strengthening methods cannot achieve high strength and high toughness at high temperatures, significantly improves the comprehensive performance of Mo alloys, and meets the demand for key structural materials in space reactors.
Patent Information
- Application Number
- CN202510001241.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2045-01-02
AI Technical Summary
Traditional nanoparticles as diffuse particle-strengthening Mo alloys cannot achieve the strong plasticity of Mo alloy materials, and cannot achieve high strength and high toughness at high temperatures, which cannot meet the demand for key structural materials in space reactors.
The in-situ high-stable nanometal particle dispersion-enhanced Mo alloy was prepared by powder metallurgy method. The boride ceramic powder HfB2 was introduced into the source of B and reacted with the impurity O in Mo to generate nanocube structure Hf particles uniformly distributed inside the Mo grains.
The toughness and strength of Mo alloys are significantly improved. The ultimate tensile strength can reach 754MPa and the elongation can reach ~22.5% at high temperatures of 400 ℃. The strong plasticity is better than that of pure Mo and Mo alloys with wide applications in the industry.
Smart Images

Figure CN119640119A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of Mo alloy structural materials, and in particular relates to an in-situ generated highly stable nano metal particle dispersion-enhanced Mo alloy and a preparation method thereof. Background Art
[0002] Mo alloy has a high melting point of ~2620 ℃, good high temperature strength, corrosion resistance, good thermal conductivity and other excellent physical and chemical properties. At the same time, it has been widely used in aerospace engineering as a high temperature resistant structural material. Although Mo has many performance advantages, pure Mo still has problems such as poor room temperature plasticity, low high temperature strength, recrystallization brittleness and radiation embrittlement, which greatly limits the application range of Mo.
[0003] Traditionally, the research and development of high-performance Mo alloys mainly involves fine grain strengthening, solid solution strengthening, and dispersion strengthening. Fine grain strengthening mainly improves the strength of metals by refining the grain size of polycrystalline materials; solid solution strengthening is a phenomenon in which the strength and hardness of the matrix are increased by local lattice distortion caused by solute atoms. Both of these strengthening mechanisms can only improve the strength of the material, while dispersion strengthening can synergistically solve the comprehensive properties of the material such as mechanics and thermal properties. Dispersion strengthening is to disperse and strengthen Mo grains and grain boundaries by introducing uniformly dispersed nanoparticles such as oxides Y2O3, La2O3 or carbides ZrC, TiC, etc. According to the strengthening mechanism in Mo alloys doped with dispersed particles, the dispersed particles in Mo grains are more effective in improving the strength and toughness of the material than the dispersed particles dispersed at the grain boundaries. Mainly, the particles dispersed between grains tend to gather at the grain boundaries, which will become stress concentration points during subsequent tensile deformation or service, and may cause cracking between the particles and the Mo matrix. For example, Cheng et al. reported in the paper entitled “Coupling effect of intergranular and intragranular particles on ductilefracture of Mo–La2O3 alloys”, Materials Science & Engineering A, 640 (2015) 320329, that by adding La2O3 to Mo, La2O3 was used as a dispersed particle to strengthen the Mo alloy, and the intergranular particle size reached 230 nm and the proportion of particles distributed at the grain boundaries was as high as 28%.
[0004] In summary, traditional nanoparticles as dispersed particles to strengthen Mo alloys cannot have both the strong plasticity of Mo alloy materials and cannot achieve high strength, high toughness and other problems at high temperatures. The comprehensive mechanical properties of Mo alloys cannot be further improved and cannot meet the needs of space reactors for key structural materials. In view of the existence of the above problems, the present invention proposes an in-situ generated high-stability nano-metal particle dispersion-reinforced Mo alloy and a preparation method thereof. Summary of the invention
[0005] The purpose of the present invention is to provide an in-situ generated highly stable nano metal particle dispersion reinforced Mo alloy and a preparation method thereof in order to solve the above problems.
[0006] The present invention achieves the above-mentioned purpose through the following technical solutions: The present invention provides an in-situ generated highly stable nano metal particle dispersion reinforced Mo alloy, wherein the Mo alloy is prepared by pressure sintering through a powder metallurgy method; The Mo alloy comprises, by mass percentage, 0.4-0.7wt% of boride ceramic powder HfB2 and 99.3-99.6wt% of metal Mo powder; The microstructure of the Mo alloy includes Mo grains and Hf particles with a nano-cubic structure uniformly distributed inside the Mo grains.
[0007] As a further optimization scheme of the present invention, the average particle size of the boride ceramic powder HfB2 is 50-500 nm, and the average particle size of the metal Mo powder is 0.5-5.0 μm.
[0008] As a further optimization solution of the present invention, in the microstructure of the Mo alloy, the average particle size of the Mo grains is 6.7 μm.
[0009] As a further optimization scheme of the present invention, in the microstructure of the Mo alloy, more than 80% of the Hf particles are evenly distributed inside the Mo grains, and the remaining particles are distributed at the grain boundaries of the Mo grains.
[0010] The present invention also provides a method for preparing the in-situ generated highly stable nano-metal particle dispersion-reinforced Mo alloy as described above, which is made by powder metallurgy and comprises the following steps: Step 1: According to the formula, metal Mo powder and boride ceramic powder HfB2 are placed in a protective atmosphere or vacuum or alcohol and mixed evenly to obtain a mixed powder; Step 2: Place the mixed powder obtained in step 1 into a graphite mold, then place the graphite mold in a vacuum or protective atmosphere, and sinter under pressure at 1500-1800 °C for 1-10 h. Finally, cool in the furnace to obtain a Mo alloy sintered block.
[0011] As a further optimization scheme of the present invention, in steps one and two, the protective atmosphere is one of a hydrogen atmosphere, a nitrogen atmosphere, an argon atmosphere, a helium atmosphere or a neon atmosphere.
[0012] As a further optimization scheme of the present invention, in steps one and two, the vacuum degree of the vacuum condition is ≤ 20 Pa.
[0013] As a further optimization scheme of the present invention, in step 2, the pressure condition of the pressure sintering is 21 kN.
[0014] The beneficial effects of the present invention are: The preparation process of the present invention is simple. The B source is introduced through the boride ceramic powder HfB2 to react with the impurity O in Mo to generate B2O3 to purify the grain boundaries and react in situ to generate Hf with a nano cubic structure uniformly distributed inside the Mo grains. Most of the particles are uniformly distributed inside the Mo grains, which can solve the problem that traditional dispersion-strengthened Mo alloy particles are prone to agglomeration at the grain boundaries, resulting in performance degradation in subsequent service and even becoming a crack source, thereby greatly improving the toughness and strength of Mo.
[0015] The present invention develops a temperature-raising and pressure-applying sintering process, and the simultaneous application of pressure while heating can effectively increase the density of the material and significantly improve the performance of the material.
[0016] Performance tests show that the Mo alloy prepared in the present invention has an ultimate tensile strength of 754 MPa and an elongation of ~22.5% at a high temperature of 400°C, and both strength and plasticity are significantly better than pure Mo and Mo alloys that are widely used in industry.
[0017] Furthermore, the present invention subjected the sintered sample to a high temperature annealing treatment at 1000 °C for 100 h, and characterized the microstructure and mechanical properties of the sample after the high temperature annealing treatment. The results showed that after the high temperature annealing, most of the particles in the microstructure were still evenly dispersed inside the Mo grains, and the tensile properties at a high temperature of 400 °C were comparable to those of the sintered sample. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 It is the sintering process curve provided by the present invention; Figure 2 This is the result of element line scanning using an energy dispersive spectrometer (EDS) tester on the sintered high-strength and toughness Mo alloy prepared in Example 1 of the present invention; Figure 3 The electron backscattering results of the pure Mo sintered body (a) prepared in Comparative Example 1 of the present invention and the sintered high-strength and toughness Mo alloy (b) obtained in Example 1; Figure 4The transmission electron microscopy results of the sintered high-strength and toughness Mo alloy (a) obtained in Example 1 of the present invention and the Mo-HfO2 alloy (b) obtained in Comparative Example 2; Figure 5 The tensile engineering stress-strain curves of the sintered high-strength and toughness Mo alloy (a) obtained in Example 1 of the present invention and the Mo-HfO2 alloy (b) obtained in Comparative Example 2 at 400°C are shown. DETAILED DESCRIPTION
[0019] The present invention is further described in detail below in conjunction with the accompanying drawings. It is necessary to point out here that the following specific implementation methods are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Technicians in this field can make some non-essential improvements and adjustments to the present invention based on the above application content.
[0020] In the following examples, metal Mo powder is obtained by commercial purchase or by conventional methods in the art, and boride ceramic powder HfB2 is obtained by boron thermal reduction method with a purity of 99%.
[0021] Example 1 The sintered high-strength and toughness Mo alloy disclosed in this embodiment is made by powder metallurgy, and the preparation method includes the following steps: Step 1: 99.3 wt% of metal Mo powder and 0.7 wt% of boride ceramic powder HfB2 are uniformly mixed by mechanical ball milling in an argon atmosphere to obtain a mixed powder, wherein the average particle size of the metal Mo powder is about 2.0 μm, and the average particle size of the boride ceramic powder HfB2 is about 170 nm; Step 2: Place the mixed powder obtained in step 1 into a graphite mold, and then place the graphite mold under a vacuum condition with a vacuum degree of 20 Pa. Figure 1 The powder was densified and sintered by the three-step heating and two-step pressurizing method shown in the figure, and the temperature was kept for 2 hours. Finally, the sintered high-strength and toughness Mo alloy was obtained after cooling in the furnace.
[0022] The microstructure and mechanical properties of the sintered high-strength and tough Mo alloy prepared in Example 1 were analyzed.
[0023] Figure 2 The EDS spectrum photo of the sintered high-strength and tough Mo alloy is shown. It can be seen from the figure that the structure of the sintered high-strength and tough Mo alloy consists of a Mo matrix and Hf particles with a nano-cubic structure. The boride ceramic powder HfB2 reacts in situ with the impurity oxygen in Mo, absorbs the impurity oxygen in the grain boundary, reduces the embrittlement effect of the impurity oxygen on Mo, and generates a Hf particle dispersion-strengthened Mo alloy. Figure 3(b) shows the electron backscattering result of the sintered high-strength and toughness Mo alloy obtained in Example 1. It can be seen from the figure that the density of the sintered high-strength and toughness Mo alloy is 99%, and the average particle size of the Mo grains is 6.7 μm.
[0024] Figure 4 (a) shows the transmission electron microscopy result of the sintered high-strength and toughness Mo alloy obtained in Example 1. As can be seen from the figure, the position indicated by the arrow shows that most of the particles are evenly distributed inside the Mo grains.
[0025] Figure 5 The tensile engineering stress-strain curve of the sintered high-strength and tough Mo alloy at 400°C obtained in Example 1. It can be seen from the figure that at 400°C, the ultimate tensile strength of the sintered high-strength and tough Mo alloy is about 754MPa and the elongation is ~22.5%.
[0026] Example 2 The sintered high-strength and toughness Mo alloy disclosed in this embodiment is made by powder metallurgy, and the preparation method includes the following steps: Step 1: 99.5 wt% of metal Mo powder and 0.5 wt% of boride ceramic powder HfB2 are mixed uniformly by mechanical ball milling in an argon atmosphere to obtain a mixed powder; wherein the average particle size of the metal Mo powder is about 2.0 μm, and the average particle size of HfB2 is about 170 nm; Step 2: Place the mixed powder obtained in step 1 into a graphite mold, then place the graphite mold under a vacuum condition with a vacuum degree of 20 Pa, and Figure 1 The sintering process curve shown in the figure is used for pressure sintering under the sintering conditions defined by the sintering process curve, and the temperature is kept for 2 hours. Finally, the sintered high-strength and toughness Mo alloy is obtained after cooling in the furnace.
[0027] According to the test, the sintered high-strength and tough Mo alloy obtained in Example 2 has an ultimate tensile strength of about 700 MPa and an elongation of ~17% at 400°C.
[0028] Example 3 The sintered high-strength and toughness Mo alloy disclosed in this embodiment is made by powder metallurgy, and the preparation method includes the following steps: Step 1: 99.4 wt% of metal Mo powder and 0.6 wt% of boride ceramic powder HfB2 are mixed uniformly by mechanical ball milling in an argon atmosphere to obtain a mixed powder; wherein the average particle size of the metal Mo powder is about 2.0 μm, and the average particle size of HfB2 is about 170 nm; Step 2: Place the mixed powder obtained in step 1 into a graphite mold, then place the graphite mold under a vacuum condition with a vacuum degree of 20 Pa, and take the following steps: Figure 1 The powder was densified and sintered by the three-step heating and two-step pressurizing method shown in the figure, and the temperature was kept for 2 hours. Finally, the sintered high-strength and toughness Mo alloy was obtained after cooling in the furnace.
[0029] According to the test, the sintered high-strength and tough Mo alloy obtained in Example 3 has an ultimate tensile strength of about 720 MPa and an elongation of ~20% at 400°C.
[0030] Example 4 The sintered high-strength and toughness Mo alloy disclosed in this embodiment is made by powder metallurgy, and the preparation method includes the following steps: Step 1: 99.6wt% of metal Mo powder and 0.4wt% of boride ceramic powder HfB2 are mixed uniformly by mechanical ball milling in an argon atmosphere, wherein the average particle size of the metal Mo powder is about 2.0 μm, and the average particle size of HfB2 is about 170 nm, to obtain a mixed powder; Step 2: Place the mixed powder obtained in step 1 into a graphite mold, then place the graphite mold under a vacuum condition with a vacuum degree of 20 Pa, and take the following steps: Figure 1 The powder was densified and sintered by the three-step heating and two-step pressurizing method shown in the figure, and the temperature was kept for 2 hours. Finally, the sintered high-strength and toughness Mo alloy was obtained after cooling in the furnace.
[0031] According to tests, the sintered high-strength and toughness Mo alloy obtained in Example 4 has an ultimate tensile strength of about 700 MPa and an elongation of about 18% at 400°C.
[0032] Comparative Example 1 The pure Mo sintered block disclosed in this comparative example is made by powder metallurgy, and the preparation method comprises the following steps: Step 1: 100 wt% metal Mo powder is uniformly milled by mechanical ball milling in an argon atmosphere, and the average particle size of the metal Mo powder is about 2.0 μm; Step 2: Put the metal Mo powder treated in step 1 into a graphite mold, then place the graphite mold under a vacuum condition with a vacuum degree of 20Pa, and take the following steps: Figure 1 The powder was densified and sintered by the three-step heating and two-step pressurizing method shown in the figure, and the temperature was kept for 2 hours. Finally, the pure Mo sintered block was obtained after cooling in the furnace.
[0033] Figure 3 (a) shows the electron backscattering result of the pure Mo sintered block obtained in Comparative Example 1. It can be seen from the figure that the average particle size of the Mo grains in the pure Mo sintered block is 15.8 μm. The sintered high-strength and toughness Mo alloy obtained in Example 1 has Mo grains refined by about 9.1 μm compared with the pure Mo sintered block.
[0034] In addition, tests show that the sintered pure Mo alloy obtained in Comparative Example 1 has no plasticity at 400°C.
[0035] Comparative Example 2 Different from Example 1, in this comparative example, the metal Mo is dispersed and enhanced by using oxide ceramic powder HfO2 to obtain Mo-HfO2 alloy, and the preparation method includes the following steps: Step 1: 99.3 wt% of metal Mo powder and 0.7 wt% of oxide ceramic powder HfO2 are mixed uniformly by mechanical ball milling in an argon atmosphere to obtain a mixed powder, wherein the average particle size of the metal Mo powder is about 2.0 μm, and the average particle size of the HfO2 powder is 40 nm; Step 2: Place the mixed powder obtained in step 1 into a graphite mold, then place the graphite mold under a vacuum condition with a vacuum degree of 20 Pa, and take the following steps: Figure 1 The powder was densified and sintered by the three-step heating and two-step pressurizing method shown in the figure, and the temperature was kept for 2 hours. Finally, the Mo-HfO2 alloy was obtained after cooling in the furnace.
[0036] Figure 4 (b) shows the transmission electron microscopy result of the Mo-HfO2 alloy obtained in Comparative Example 2. As can be seen from the figure, the position indicated by the arrow shows that most of the HfO2 particles are distributed at the grain boundary of the Mo grains, which will cause the Mo alloy material to have performance degradation or even become a crack source during service, which is not conducive to improving the strength and toughness of the alloy material.
[0037] Figure 5 The tensile engineering stress-strain curve of the Mo-HfO2 alloy at 400°C is given. It can be seen from the figure that at 400°C, the ultimate tensile strength and elongation of the Mo-HfO2 alloy are lower than those of the sintered high-strength and tough Mo alloy obtained in Example 1. The elongation of the sintered high-strength and tough Mo alloy obtained in Example 1 is increased by about 7% compared with the Mo-HfO2 alloy.
[0038] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.
Claims
1. An in-situ generated highly stable nano-metal particle dispersion-enhanced Mo alloy, characterized in that: The Mo alloy is prepared by powder metallurgy and pressure sintering; wherein, the Mo alloy comprises, by mass percentage, 0.4-0.7wt% of boride ceramic powder HfB2 and 99.3-99.6wt% of metal Mo powder; the microstructure of the Mo alloy comprises Mo grains and Hf particles with nano-cubic structure uniformly distributed inside the Mo grains.
2. The in-situ generated highly stable nano-metal particle dispersion-enhanced Mo alloy according to claim 1, characterized in that: The average particle size of the boride ceramic powder HfB2 is 50-500 nm, and the average particle size of the metal Mo powder is 0.5-5.0 μm.
3. The in-situ generated highly stable nano-metal particle dispersion-enhanced Mo alloy according to claim 1, characterized in that: In the microstructure of the Mo alloy, the average particle size of Mo grains is 6.7 μm.
4. The in-situ generated highly stable nano-metal particle dispersion-enhanced Mo alloy according to claim 1, characterized in that: In the microstructure of the Mo alloy, more than 80% of the Hf particles are evenly distributed inside the Mo grains, and the remaining particles are distributed at the grain boundaries of the Mo grains.
5. A method for preparing an in-situ generated highly stable nano-metal particle dispersion-reinforced Mo alloy as claimed in any one of claims 1 to 4, made by powder metallurgy, characterized in that: The following steps are involved: Step 1: According to the formula, metal Mo powder and boride ceramic powder HfB2 are placed in a protective atmosphere or vacuum or alcohol and mixed evenly to obtain a mixed powder; Step 2: Place the mixed powder obtained in step 1 into a graphite mold, then place the graphite mold in a vacuum or protective atmosphere, and sinter under pressure at 1500-1800 °C for 1-10 h. Finally, cool in the furnace to obtain a Mo alloy sintered block.
6. The method for preparing an in-situ generated highly stable nano-metal particle dispersion-reinforced Mo alloy according to claim 5, characterized in that: In steps 1 and 2, the protective atmosphere is one of a hydrogen atmosphere, a nitrogen atmosphere, an argon atmosphere, a helium atmosphere or a neon atmosphere.
7. The method for preparing an in-situ generated highly stable nano-metal particle dispersion-enhanced Mo alloy according to claim 5, characterized in that: In steps 1 and 2, the vacuum degree of the vacuum condition is ≤ 20 Pa.
8. The method for preparing an in-situ generated highly stable nano-metal particle dispersion-reinforced Mo alloy according to claim 5, characterized in that: In step 2, the pressure condition of the pressure sintering is 21 kN.
Citation Information
Patent Citations
In-situ synthesized Al2O3 reinforced molybdenum based composite material and preparation method thereof
CN101392347A
Preparation method of Mo2B-reinforced molybdenum alloy
CN104060115A
In-situ generated molybdenum carbide reinforced molybdenum-based composite material and preparation method thereof
CN109371304A
In-situ endogenous multiphase nano oxide dispersion reinforced Mo alloy and preparation method thereof
CN117983807A
High-entropy nano oxide particle reinforced W alloy generated through in-situ solid-phase reaction and preparation method of high-entropy nano oxide particle reinforced W alloy
CN117987679A